Development and Evaluation of a Nurse Leadership Succession Planning Strategy in an Academic Medical Center. (July 2020) - Morris, Matthew; Wood, Felecia; Dang, Deborah
Abstract : Absence of nurse manager succession planning in an academic medical center necessitated a quality improvement project to identify, select, and enroll emerging leaders into a development program. The authors used organizational competencies and an evidence-based approach to effectively identify barriers, select future nurse leaders, and discover opportunities for process improvement. Abstract : Supplemental digital content is available in the text.